FEATURES OF THE INCENTIVES WORK AND MOTIVATIONAL PROCESSES SYSTEM IN THE RAILWAY INDUSTRY IN THE PERIOD OF UKRAINIAN ECONOMY TRANSFORMATION - Hetmanenko, O. V. (Science and Transport Progress, 2008)
Systems of the labour stimuli and realization of the motivation processes in the railway branch during the period of transformation of the economy ofUkraineare considered.